"Flags and Slots": Special Interest Groups and Selective Admissions - Lang, Katherine E.; Lang, Daniel W. (Canadian Journal of Higher Education, 2002)
This paper combines the results of two studies, one from the perspective of institutions and one from the perspective of students, to determine and define the role played by special interest groups in selecting students for admission to college and university. Although there have been allusions to the existence of selection processes that categorize applicants in terms of various special talents and skills, and of racial, ethnic, or geographic origin, relatively little is known about how wide- spread those processes are and how they actually operate at highly selective colleges and universities. Also, little is known about how special interest group selection is perceived by applicants and their schools. The studies indicate how and why special interest group selection works, and shows that the process is widely used. The studies also indicate that, although applicants are aware of the process, their perception of it does not coincide with either the motives or the expectations of the colleges and universities that deploy it.